Formulación De Un Manual De Seguridad Industrial Y Salud Ocupacional Para La Empresa Ilelsa De La Ciudad De Loja” - Criollo Quezada, Jonathan Javier (2016)
The Integrated Security is a new concept which covers the Industrial Safety, Industrial Hygiene , Occupational Health , Loss Control and Environment and integrates the production processes of modern enterprises in order to improve working conditions and the working environment of all its workers. This concept integrates all the security personnel of the company, from top management to operational levels of workers. Identifying the various physical, chemical, biological and ergonomic hazards to which workers are exposed as a result of their daily operations in all production processes lead us to take control and prevention measures to avoid accidents and occupational diseases can be caused by prolonged exposure to these different types of risks. Comprehensive Security in the quality and productivity are also integrated as they have similar backgrounds and the same goal: greater competitiveness. In this thesis an analysis of the current situation in Bottling Company ILELSA Liquor Industry, the same dedicated to the production and marketing of its main product Cantaclaro and distribution of beverages, and consumer products was performed massive. Us ILELSA not have a manual Occupational Health and Safety which can become a serious problem, which is why it is appropriate to its preparation by the present thesis for the respective corrections are taken with respect to physical hazards, chemical and ergonomic that are present in the different production processes in every area of the company, as well as fire hazards because it is a company that uses feedstock flammable products. Through measurements of noise levels in all production areas of the company can be seen with values which are the areas that pose the greatest risk of acquiring an occupational disease for workers who are exposed to these risks, and also identify per job which are those that produce a higher level of noise. We also analyzed the Ergonomic Hazards, how workers clearance area Manipulating Loads finished product, in this case the cartons so as to assess the physical effort made by them. Risk of Fire Company considering the Thermal Load of its main materials that could become fuel in the event of a fire was analyzed. With the implementation of suggested recommendations is expected that the company ILELSA launching Manual Industrial Safety and Occupational Health improve the functioning of the company in mind to quickly identify the risks they are exposed personnel and the company itself and thus correct them , training staff so you can properly respond well of themselves and the institution.